Applying an outcomes-based categorisation to non-warranted/non-sworn volunteers in United States policing. (March 2020) - Wolf, Ross; Bryer, Thomas
The use of volunteers for government service can improve civic engagement, collaboration in governance, and transparency. Policing is no exception, and throughout the United States many police agencies rely on volunteers to serve in various ways, including observational patrols, investigations, administrative support, chaplains, police explorer programmes, and search and rescue teams. While there are police volunteers in the United States that have police powers, this manuscript focuses on the varied ways that citizens participate in policing in non-warranted/non-sworn roles, and applies an outcomes-based categorisation to better understand motivations. Examples of volunteerism are provided, and the variation of use is discussed.